2023
DOI: 10.3389/fpsyg.2023.1221648
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and asthma: a systematic review

Orlando Silvestro,
Luisa Ricciardi,
Antonino Catalano
et al.

Abstract: Growing evidence from scientific research elucidates the important role of alexithymia in chronic immune diseases. This Review aims to explore the presence of alexithymia in patients affected by asthma and clarify its associations with other involved psychological and physical factors. In January 2023, according to PRISMA guidelines, a systematic search using PubMed and Scopus was conducted. Twenty-six studies were eligible based on inclusion criteria. Alexithymia was significantly present in asthma patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…The use of rapid assessment tools such as the WWBI, Six-item screener (SIS), and CLOX-1 in EDs has been gaining attention for their potential to improve patient outcomes through assessing psychological well-being and cognition (26,27). Older adults individuals have cardiovascular diseases, particularly diabetes, and hypertension, as well as thyroid disorders and asthma as co-morbidities, and this in turn leads to a decline in cognition (2,3,6,8,24,(28)(29)(30)(31)(32)(33). However, literature comparing the three tests and identifying positive associations between them is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rapid assessment tools such as the WWBI, Six-item screener (SIS), and CLOX-1 in EDs has been gaining attention for their potential to improve patient outcomes through assessing psychological well-being and cognition (26,27). Older adults individuals have cardiovascular diseases, particularly diabetes, and hypertension, as well as thyroid disorders and asthma as co-morbidities, and this in turn leads to a decline in cognition (2,3,6,8,24,(28)(29)(30)(31)(32)(33). However, literature comparing the three tests and identifying positive associations between them is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia concerns the difficulty in describing, interpreting and identifying affective experiences. The role of alexithymia in chronic medical difficulties has often been emphasized in clinical research but must be considered within the context of the developmental stage of the medical condition [23][24][25][26][27][28][29][30][31][32]. The role of alexithymia in mental health difficulties is known in the literature, especially with reference to people experiencing chronic conditions [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…The role of alexithymia in chronic medical difficulties has often been emphasized in clinical research but must be considered within the context of the developmental stage of the medical condition [23][24][25][26][27][28][29][30][31][32]. The role of alexithymia in mental health difficulties is known in the literature, especially with reference to people experiencing chronic conditions [25,27]. Shang and colleagues [26] testify to the relationships between alexithymia and chronic conditions, identifying alexithymia as a significant predictor for the onset and maintenance of chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Peter Sifneos coined the term, which means "no words for mood" to describe a cluster of cognitive and affective characteristics, including "operational thinking", initially observed among patients with psychosomatic diseases [7]. Several recent studies have demonstrated an important relationship between alexithymia and psychiatric disorders, drug abuse, personality disorders, and various medical diseases [8][9][10][11]. Currently, the frequency of alexithymia ranges between 9 and 23% in the general population, according to several studies [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%